1998
DOI: 10.3141/1644-02
|View full text |Cite
|
Sign up to set email alerts
|

Linear Acceleration Car-Following Model Development and Validation

Abstract: A linear acceleration car-following model has been developed for realistic simulation of traffic flow in intelligent transportation systems (ITS) applications. The new model provides continuous acceleration profiles instead of the stepwise profiles that are currently used. The brake reaction times of the drivers are simulated effectively and are independent of the simulation time steps. Chain-reaction times of the drivers are also simulated and perception thresholds are incorporated in the model. The preferred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 3 publications
2
14
0
Order By: Relevance
“…It emerged from the data analysis that car-following conditions occur, in accordance with Aycin and Benekohal's theory [31], for distances of less than 75 metres: in fact, for distances greater than that critical value, user behaviour does not prove to be in any way influenced by preceding vehicles in the same lane.…”
Section: Data Gatheringsupporting
confidence: 68%
“…It emerged from the data analysis that car-following conditions occur, in accordance with Aycin and Benekohal's theory [31], for distances of less than 75 metres: in fact, for distances greater than that critical value, user behaviour does not prove to be in any way influenced by preceding vehicles in the same lane.…”
Section: Data Gatheringsupporting
confidence: 68%
“…Bham argued that the follower accelerates in case when the space gap is greater than three times their current speed [21]. 1 s equivalent to time step and reaction time or "lag" for all the vehicles is suggested by Bham and Aycin [21,42]. In this study, the model parameter values are s min = 2 m, s safe = 3 × v t+1 (m), timestep = 1 s. The design speed is set to 60 km/h.…”
Section: Model Calibrationmentioning
confidence: 98%
“…Some past researchers showed that a wide range of factors such as drivers' behavior, traffic condition, road condition, roadway design, state law and regulation, and even personality had effects on vehicle headway (Ayres et al 2001;Aycin and Benekohal 1998;Brackstone and McDonald 1999;Hogema 1999;Brackstone 2003;Rajalin, Hassel, and Summala 1997). Based on these factors, various car following models were developed to describe the interaction between individual vehicles or the whole traffic dynamic.…”
Section: Tailgating Issuesmentioning
confidence: 99%